Estimation of prevalence of headphone usage during driving and awareness about their health hazards among medical undergraduates - Pandey, Dhruvendra; Saroshe, Satish; Dixit, Sanjay; Sabde, Yogesh (International Journal Of Community Medicine And Public Health, 2017)
Background: As year passes, numbers of vehicles on road are increasing at the same time numbers of accidents are increasing. One of the major contributors for these accidents is the distraction created by headphone use during driving. Youngsters which are the major contributor for any nation’s development are lost due to these accidents. Aims: To estimate prevalence of headphone use while driving among medical graduates and find out felt problems associated with headphone usage while driving. Methods: Setting and design: An observation (Cross-sectional) study was conducted in government medical college situated in urban area.Technique: 260 medical under graduate were selected for study. A semi structured questionnaire was used as study tool for observation. Written informed consent was obtained from all the participants.Statistical analysis used: The data was analyzed using appropriate statistical software (MS excel). Results: In this Study out of 260 medical undergraduates, 192 (73.85%) boys and 68 (26.15%) girls participated. 37.30% students were using headphone during driving out of which 20.77% were always using with every drive and 16.53% were occasionally using headphone. Only 71 (27.31%) student were not using helmet during driving. 37.11% students used headphone for both talking and listening songs, they prefer to listen songs in high volume (21.65%). 65% students had knowledge about health hazards associated with headphone usage. Conclusions: Prevalence of headphone usage during driving among medical undergraduates was found to be 37.3%. Despite of the awareness of health hazards associated with headphone usage, most of the students prefer headphone over helmet.